Microscopy and outpatient malaria case managementamong older children and adults in Kenya - Zurovac, D; Midia, B; Ochola, S . A; English, M; Snow, R. W (Published online in Wiley InterScience (www.interscience.wiley.com), 2006)
To evaluate the accuracy of routine malaria microscopy, and appropriate use andinterpretation of malaria slides under operational conditions in Kenya.methods Cross-sectional survey, using a range of quality of care assessment tools, at governmentfacilities with malaria microscopy in two Kenyan districts of different intensity of malaria transmission.All patients older than 5 years presenting to outpatient departments were enrolled. Two expertmicroscopists assessed the accuracy of the routine malaria slide results.results We analysed 359 consultations performed by 31 clinicians at 17 facilities. Clinical assessmentwas suboptimal. Blood slide microscopy was performed for 72.7% of patients, who represented 78.5%of febrile patients and 51.3% of afebrile patients. About 95.5% of patients with a positive malariamicroscopy result and 79.3% of patients with a negative result received antimalarial treatment.Sulphadoxine–pyremethamine monotherapy was more commonly prescribed for patients with anegative test result (60.7%) than for patients with a positive result (32.4%). Conversely, amodiaquine orquinine were prescribed for only 14.7% of patients with a negative malaria microscopy result comparedto 57.7% of patients with a positive result. The prevalence of confirmed malaria was low in both high(10.0%) and low-(16.3%) transmission settings. Combining data from both settings, the sensitivity ofroutine microscopy was 68.6%; its specificity, 61.5%; its positive predictive value, 21.6% and itsnegative predictive value, 92.7%.conclusions The potential benefits of microscopy are currently not realised because of the poor qualityof routine testing and irrational clinical practices. Ambiguous clinical guidelines permitting treatment ofolder children and adults with a negative blood slide also undermine rational use of antimalarial drugs
full text
Keywords: malaria, microscopy, interpretation, accuracy, Kenya